Multi-spatial resolution hyperspectral image change detection network integrating feature difference structure - Yanhua Xiao; Shuixiang Yu; Wenfeng Li; Huafei Xiao; Yiling Chen; Huayan Zhou; Long Yang (PLoS ONE, 2026)
Change detection (CD) can detect changes in the earth’s surface. However, the existing Siamese network-based CD methods usually calculate the Euclidean distance (ED) between two branches to obtain difference features, ignoring the deeper feature disparities captured by the CNN. In addition, the patch obtained in the CD method using spatial information may have the phenomenon that the adjacent pixels and the pixels to be classified are not the same object or change type. To deal with the aforementioned challenges, we propose FDS-BINet, a multi-spatial resolution network integrating a Feature Difference Structure (FDS) and Bicubic Interpolation (BI). The FDS module progressively extracts deep pixel-level differences through residual-enhanced Siamese branches, while BI interpolates the absolute distance spectrum to recover subpixel-level changes. The main contributions of this article are as follows: 1) A change detection framework called FDS-BINet has been proposed that fuses pixel-level and subpixel-level change information. 2) A feature difference structure (FDS) is designed to obtain deep difference features of pixel-level spatial information of bitemporal HSIs; 3) The bicubic interpolation (BI) algorithm is used for absolute distance (AD) spectrum interpolation. We can effectively boost the spatial resolution of AD spectrum data, enabling us to extract feature differences at the subpixel level from bitemporal hyperspectral images (HSIs). The experimental results demonstrate that the proposed FDS-BINet has better performance compared with representative methods in the field of HSI CD.